2014
DOI: 10.1039/c3md00288h
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence: a versatile technique for imaging cellular and molecular features

Abstract: Bioluminescence is a ubiquitous imaging modality for visualizing biological processes in vivo. This technique employs visible light and interfaces readily with most cell and tissue types, making it a versatile technology for preclinical studies. Here we review basic bioluminescence imaging principles, along with applications of the technology that are relevant to the medicinal chemistry community. These include noninvasive cell tracking experiments, analyses of protein function, and methods to visualize small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
129
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 176 publications
(320 reference statements)
1
129
0
3
Order By: Relevance
“…S4A). Similar flash-type light emission kinetics are observed with D-luciferin, where the decay results from enzyme inhibition by luciferin/luciferase reaction byproducts (41,42,44). The similarity in light emission kinetics in the presence and absence of copper treatment suggests that bioluminescence results from luciferase reaction with the same substrate, namely D-luciferin.…”
Section: Ccl-1 Detects Changes In Labile Copper Levels In Living Cellssupporting
confidence: 51%
See 2 more Smart Citations
“…S4A). Similar flash-type light emission kinetics are observed with D-luciferin, where the decay results from enzyme inhibition by luciferin/luciferase reaction byproducts (41,42,44). The similarity in light emission kinetics in the presence and absence of copper treatment suggests that bioluminescence results from luciferase reaction with the same substrate, namely D-luciferin.…”
Section: Ccl-1 Detects Changes In Labile Copper Levels In Living Cellssupporting
confidence: 51%
“…Luciferin-based bioluminescence imaging is an attractive modality for in vivo use owing to its low background signal, efficient photon production, and good tissue penetration of its red-shifted emission (40)(41)(42). Moreover, impressive advances in luciferase engineering and ease of targeting by genetic encoding permit the broad use of such reporters for in vivo imaging with cell and tissue specificity (41,43,44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, luciferase types using substrate D-luciferin show stable luminescence photon counts in sustained measurement. 13 Therefore, ELuc, which is an extremely bright luciferase using D-luciferin, was chosen for the imaging assay. 14 In an earlier study using ELuc, we demonstrated the potential of a split luciferase fragment complementation assay with GPCR protein, β2-adrenergic receptor (ADRB2), and β-arrestin2.…”
Section: Resultsmentioning
confidence: 99%
“…used as "microbial biosensors" [8], for example, for detection of toxic materials. Also, the ability to track the light-emitting cells within an organism provides powerful in vivo imaging technology [9]. Bioluminescence technologies have been applied in research on drugs, cancer, bacterial infectious diseases, etc.…”
Section: Box 63 Electricity and The Cellmentioning
confidence: 99%